2021
DOI: 10.1186/s12864-020-07321-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis reveals genetic variations and candidate genes associated with salt tolerance related traits in Gossypium hirsutum

Abstract: Background Cotton is more resistant to salt and drought stresses as compared to other field crops, which makes itself as a pioneer industrial crop in saline-alkali lands. However, abiotic stresses still negatively affect its growth and development significantly. It is therefore important to breed salt tolerance varieties which can help accelerate the improvement of cotton production. The development of molecular markers linked to causal genes has provided an effective and efficient approach for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Salt tolerance is a complex quantitative trait, which is controlled by multiple genes and involves a variety of physiological and biochemical metabolic pathways in cotton [ 6 ]. Quantitative trait locus (QTL) mapping of salt-related traits has become an effective approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt tolerance is a complex quantitative trait, which is controlled by multiple genes and involves a variety of physiological and biochemical metabolic pathways in cotton [ 6 ]. Quantitative trait locus (QTL) mapping of salt-related traits has become an effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Many QTLs were mapped on A05, A08, A09, A11, D01, D08, D09, D10 and D12 for salt tolerance in tetraploid cotton. Xu et al (2021) found a locus on chromosome A13 and D08 associated with relative plant height (RPH), and loci on A07 for relative shoot fresh matter weight (RSFW); A08 and A13 for relative shoot dry matter weight (RSDW) were expressed in both environments and the increase in GH_A13G0171-silenced plants’ salt tolerance under salt stress indicated its negative function in regulating the salt stress response [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growth parameters, such as SRW, SDW, RFW, and RDW, have been used to determine salt stress responses and tolerance in various species, such as cotton [31], maize [32,33], tomato [34], wheat [35], eggplant [36], and rice [9]. RWC and CMS have also been used to assess salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS was conducted to identify a study’s salt tolerance-related QTLs/genes in cotton cultivars. They performed a GBS of 217 cotton cultivars and identified 12 candidate salt-tolerant genes that can be used in the breeding program for cotton improvement [ 28 ].…”
Section: Advancements In Molecular Breeding Techniquesmentioning
confidence: 99%